PENYALAHGUNAAN POSISI DOMINAN DALAM KEPEMILIKAN SAHAM SILANG - Dewi Astutty Mochtar (University of Merdeka Malang, 2013)
Unfair competition could happen because of a dominant position of an entrepreneur or businessman who hadcertain goods or service. In this case, businessman could do price regulation, price discrimination, agreementor contract with hard requirements, area distribution etc included in forbidden activities. One of activitieswhich caused the abuse of dominant position was cross share owning. The reflection of this cross share owningwas by owning majority share in some same types of companies that ran same business in the same market. Itcould also be done by building some companies having same business and same market. This thing inflictedfinancial loss to the business which finally created injustice. There were cartel practices, centered domination,etc. It was needed to regulate clearer about majority share especially the limit. If it could not be put in regulationno 5 year 1999, regulation of implementation or realization could be made.